Why Do Health Labour Market Forces Matter? - McPake, Barbara; Maeda, Akiko; Correia Araújo, Edson; Lemiere, Christophe; El Maghraby, Atef; Cometto, Giorgio (World Health Organization, 2015)
Human resources for health have been recognized as essential to the development of responsive and effective health systems. Low- and middle-income countries seeking to achieve universal health coverage face human resource constraints – whether in the form of health worker shortages, maldistribution of workers or poor worker performance – that seriously undermine their ability to achieve well-functioning health systems. Although much has been written about the human resource crisis in the health sector, labor economic frameworks have seldom been applied to analyze the situation and little is known or understood about the operation of labor markets in low- and middle-income countries. Traditional approaches to addressing human resource constraints have focused on workforce planning: estimating health workforce requirements based on a country’s epidemiological and demographic profile and scaling up education and training capacities to narrow the gap between the “needed” number of health workers and the existing number. However, this approach neglects other important factors that influence human resource capacity, including labor market dynamics and the behavioral responses and preferences of the health workers themselves. This paper describes how labor market analysis can contribute to a better understanding of the factors behind human resource constraints in the health sector and to a more effective design of policies and interventions to address them. The premise is that a better understanding of the impact of health policies on health labor markets, and subsequently on the employment conditions of health workers, would be helpful in identifying an effective strategy towards the progressive attainment of universal health coverage.